Extreme geographical fixation of variation in the Plasmodium falciparum gamete surface protein gene Pfs48 /45 compared with microsatellite loci - Conway, D.J.; Machado, Ricardo L.D.; Balbir, Singh; Dessert, Patricia; Mikes, Zsuzsanna S.; Povoa, Marinete M.; Oduola, Ayoade M.J.; Roper, Cally (Elsevier Science B.V., 2001)
Comparing patterns of genetic variation at multiple loci in the genome of a species can potentially identify loci which are under selection. The large number of polymorphic microsatellites in the malaria parasite Plasmodium falciparum are available markers to screen for selectively important loci. The Pfs48 /45 gene on Chromosome 13 encodes an antigenic protein located on the surface of parasite gametes, which is a candidate for a transmission blocking vaccine. Here, genotypic data from 255 P. falciparum isolates are presented, which show that alleles and haplotypes of five single nucleotide polymorphisms (SNPs) in the Pfs48 /45 gene are exceptionally skewed in frequency among different P. falciparum populations, compared with alleles at 11 microsatellite loci sampled widely from the parasite genome. Fixation indices measuring inter-population variance in allele frequencies (FST) were in the order of four to seven times higher for Pfs48 /45 than for the microsatellites, whether considered (i) among populations within Africa, or (ii) among different continents. Differing mutational processes at microsatellite and SNP loci could generally affect the population structure at these different types of loci, to an unknown extent which deserves further investigation. The highly contrasting population structure may also suggest divergent selection on the amino acid sequence of Pfs48/45 in different populations, which plausibly indicates a role for the protein in determining gamete recognition and compatibility.